BEST PROXIMITY POINT FOR CYCLIC CONTRACTION IN G-METRIC SPACE - Meena, Gopal; Jha, Kanhaiya (Kathmandu University Journal of Science, Engineering and Technology, 2016)
In this paper, we introduce the results of best proximity point in G-metric spaces for the cyclic contraction mapping with an example that illustrates the usability of the obtained results. Mathematics Subject Classification: 41A65, 46B85, 47H25 Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page:1-6